Percorrendo trilhos: pontes entre a proteção e a autonomia - Maria da Conceição Pinto Antunes (Centro Universitário Salesiano de São Paulo, 2016)
This paper is a result from an action-research program developed with 7 to 12 year-children/teens living under institutional care. The aim of this project was the creation of a home and family life for these children and of their empowerment through the promotion of personal, social and academic skills that enhance emancipation and independence. For the implementation of the action plan, in terms of methodology, we are guided by the qualitative paradigm; we followed a work-action-participatory research plan seeking the active involvement of the participants in sociocultural animation tasks. It was implemented through the development of five workshops about behavioral, emotional, cognitive, educational, functional and parenting skills. The data was subjected to a qualitative analysis, the results of which suggest the existence of positive and significant changes in participants' academic knowledge and school performance, as well as in what concerns to personal, relational and functional skills.